2009
DOI: 10.1177/1559827608331167
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to Promote Physical Activity Among African Americans

Abstract: This article provides a summary of recent physical activity intervention research conducted among African Americans. As prior reviews have been published in this area, the authors updated the literature by focusing on the past 8 years. Overall, there has been an increase in the number and methodological rigor of the studies in this area. Thirty studies published in peer-reviewed journals were included in the current review. Results from 18 of these studies indicated that interventions produced significant incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 29 publications
4
29
0
Order By: Relevance
“…Most physical activity intervention studies conducted among African Americans report only on short-term (i.e., less than 6 months) findings. 9,27 As the health benefits of such short-term activity gains are questionable, the emphasis needs to shift toward producing enduring changes in activity levels among African Americans.…”
Section: Computer-tailored and Internet-based Interventionsmentioning
confidence: 99%
“…Most physical activity intervention studies conducted among African Americans report only on short-term (i.e., less than 6 months) findings. 9,27 As the health benefits of such short-term activity gains are questionable, the emphasis needs to shift toward producing enduring changes in activity levels among African Americans.…”
Section: Computer-tailored and Internet-based Interventionsmentioning
confidence: 99%
“…Effective translation of research results to clinical practice depends on successful implementation and sustainability. In particular, recruitment and attrition difficulties are frequently cited challenges, and calls have been made for future research to focus on adequate recruitment and retention in order to foster sustainability and reach [15,[18][19][20]. Retention is often thought to reflect the percentage of participants that are retained for postintervention assessments, not necessarily the actual intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Historically, underserved groups have not been well represented in clinical trials to promote physical activity; however, this appears to be changing due to recent interventions more inclusive with respect to ethnic and socioeconomic diversity [13][14][15][16]. Involving communities and coalitions from the inception of research, mobilizing social networks, and targeting culturally appropriate messages and messengers all appear to be important characteristics of ethnically inclusive studies [17].…”
Section: Introductionmentioning
confidence: 99%
“…Latinos and blacks expressed interest in receiving support for physical activity through churches, but the fi ndings thus far in that setting are mixed. In fact, fi ve of the eight church-based studies reported signifi cant gains in activity behavior in a recent review of physical activity promotion in blacks [20]. Thus, church-based interventions appeal to minority participants, but more research is needed to determine their effi cacy.…”
Section: Discussionmentioning
confidence: 95%